Impact Analysis of Land Use Changes on Inundation Map In The Ciliwung River Watershed - Zein, Muhammad Raihan Arkan Abiyan; Anggraheni, Evi; Yahya, Dadang Muhamad (CSID Journal of Infrastructure Development, 2023)
The rapid population growth in Indonesia’s DKI Jakarta Province has escalated the demand for housing, increasing built-up land at the expense of green open spaces, known as Ruang Terbuka Hijau (RTH). This shift has significantly reduced the land available for water infiltration, resulting in increased runoff and flow discharge, particularly in the Ciliwung River Watershed. This research aims to map inundation in the Ciliwung River Watershed, which is attributable to land cover changes from 1990 to 2022. The study examines flood flow discharge and inundation patterns by utilizing HEC-HMS 4.10 for hydrological modeling and HEC-RAS 6.1 for 1D and 2D hydraulic models. Boundary conditions were based on recorded flood flow discharge at the Manggarai Water Gate and Katulampa Dam, combined with historical rainfall data, to represent watershed conditions accurately. Applying 1D and 2D models provides a detailed visualization of inundation changes over time. Findings reveal that identical rainfall events result in varying flood flow discharges and inundation extents due to different land covers. The Kinematic Wave routing method demonstrated high accuracy, with Nash-Sutcliffe Efficiency (NSE) and regression coefficient values of 0.93 and 0.99, respectively. The study concludes that flow discharge and inundation areas increase with the Curve Number (CN) value. Furthermore, the magnitude of rainfall return periods significantly influences discharge volumes and inundation depths, with areas experiencing 0 – 0.3 meters of flooding predominant in the Ciliwung watershed.